Kurtzmaniella hittingeri f.a., sp. nov., isolated from rotting wood and fruits, and transfer of three Candida species to the genus Kurtzmaniella as new combinations. Issue 5 (11th March 2019) - Lopes, Mariana R.; Santos, Ana Raquel O.; Moreira, Juliana D.; Santa-Brígida, Rosângela; Martins, Marlúcia B.; Pinto, Fernanda O.; Valente, Patrícia; Morais, Paula B.; Jacques, Noémie; Grondin, Cécile; Casaregola, Serge; Lachance, Marc-André; et al.
Abstract : Twelve strains of a novel yeast species were isolated from rotting wood, mushrooms and fruit samples in Brazil and French Guiana. Analysis of the sequences of the internal transcribed spacer region and the D1/D2 domains of the large subunit rRNA gene showed that the novel species belongs to the Kurtzmaniella clade. The novel species differed from its closest relative, Candida natalensis, by 12 substitutions in the D1/D2 sequences. The novel species could be distinguished from C. natalensis by its inability to assimilate cellobiose and salicin, and growth at 50 % (w/w) glucose. The name Kurtzmaniella hittingeri f.a., sp. nov. is proposed for the novel species. The type strain of K. hittingeri sp. nov. is CBS 13469 T (=UFMG CM-Y272 T ). The MycoBank number is 827183. We also propose the transfer of Candida fragi, Candida quercitrusa and Candida natalensis to the genus Kurtzmaniella as new combinations.